Bangladesh Public Expenditure Review Update : An Update of Fiscal Trends Based on the 2010 Public Expenditure Review - World Bank (World Bank, Dhaka, 2015)
This report is an update to a public expenditure review (PER) for Bangladesh undertaken in 2010. It aims to analyze the major spending trends since (and before) the PER-2010. This includes the macro-fiscal stance (deficits, debt, etc.) and the allocation of resources within the budget on both a sectoral level (health, education, etc.) and a thematic level (wages, interest, etc.). It notes whether these trends are broadly in line with stated development objectives, and whether the revenue and spending stances are sustainable. It also aims to indicate any potential issues based on the evidence presented in this report and provide an indication of the areas in which improvements or set-backs have occurred since the PER-2010, as well as whether any new issues are emerging. This report also indicates where more in-depth analytical work can be undertaken, either to confirm the findings or to gain a better understanding of an issue.